Relação entre caracteres agronômicos e anatômicos em milho - Nascimento Júnior, Ivanildo Ramalho do [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Agronomic aspects such as productivity, plant height, the ear height, susceptibility to lodging and stem breakage have quantitative inheritance, being highly influenced by the environment, making it difficult to obtain superior genotypes through direct selection of these characters. The anatomical structures are more stable and their assessment, beyond simple and low cost, can be held in the early stages of the plant, different from the agronomic aspects that need to wait for it to be expressed and evaluated. Therefore, the objective of this work was to identify the associations between the anatomical characteristics of root, stem and leaf, and agronomic in maize varieties. Studies of genetic parameters, genotypic correlation, canonical correlation, factors analysis and path analysis across the agronomic characters (plant height, ear height, ear placement, lodging, plant breakage and grain yield), anatomic root (total área of root, central cylinder area, epidermal thickness, exodermis thickness, cortical parenchyma thickness, endoderm thickness, number of metaxylem vessels, phloem area, cortex thickness and metaxylem area), the stem (average area of xylem, average area of phloem, average area of vascular bundles and number of vascular bundles) and the leaf (bulliform cells thickness, adaxial epidermis thickness, abaxial epidermis thickness, mesophyll thickness, xylem area, phloem area, sclerenchyma area, average area of vascular bundles) were performed. In the study of associations between the anatomical characters of root and agronomic observed through the canonical correlation analysis the existence of relationship between plant height and anatomical characters total area of root, central cylinder area, cortex thickness and cortical parenchyma thickness. In the study of associations between the anatomical characters of stem and agronomic, based on factors analysis, strong association between number of vascular bundles, plant height ...

Aspectos agronômicos como produtividade, estatura da planta, altura de inserção da espiga, suscetibilidade ao acamamento e quebramento do colmo apresentam herança quantitativa, sendo altamente influenciados pelo ambiente, o que dificulta a obtenção de genótipos superiores através da seleção direta desses caracteres. Já as estruturas anatômicas são mais estáveis e a sua avaliação, além de simples e de baixo custo, pode ser feita em estágios precoces da planta, diferente dos aspectos agronômicos que há necessidade de espera para que sejam expressos e assim avaliados. Sendo assim objetivou-se identificar a existência de associações entre os caracteres anatômicos da raiz, colmo e folha, e agronômicos em variedades de milho. Foram realizados estudos de parâmetros genéticos, correlação genotípica, correlação canônica, análise de fatores e de trilha através dos caracteres agronômicos (altura da planta, altura de inserção da espiga, posição relativa da espiga, acamamento, quebramento de planta e produtividade de grãos), anatômicos da raiz (área total da raiz, área do cilindro central, espessura da epiderme, espessura da exoderme, espessura do parênquima cortical, espessura da endoderme, número de vasos do metaxilema, área do floema, espessura do córtex e área do metaxilema), do colmo (área média do xilema, área média do floema, área média dos feixes vasculares e o números de feixes vasculares) e da folha (espessura das células buliformes, espessura da epiderme adaxial, espessura da epiderme abaxial, espessura do mesofilo, área do xilema, área do floema, área do esclerênquima, área média dos feixes vasculares). No estudo de associações entre os caracteres anatômicos da raiz e agronômicos observou-se através da análise da correlação canônica a existência de relação entre a altura de planta e os caracteres anatômicos área total da raiz, área do cilindro central, espessura...
Keywords: Milho; Anatomia vegetal; Genetica vegetal; Plantas - Analise; Plantas - Melhoramento genetico; Plant anatomy